2018
DOI: 10.4081/monaldi.2018.882
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and variability of use of home mechanical ventilators, positive airway pressure and oxygen devices in the Lombardy region, Italy

Abstract: Few studies have analyzed the prevalence and accessibility of home mechanical ventilation (HMV) in Italy. We aimed to investigate the prevalence and prescription variability of HMV as well as of long-term oxygen therapy (LTOT) and continuous positive airway pressure (CPAP), in the Lombardy Region. Prescribing rates of HMV (both noninvasive and tracheostomies), CPAP (auto-CPAP, CPAP/other sleep machines) and LTOT (liquid-O2, O2-gas, concentrators) in the 15 Local Healthcare districts of Lombardy were gathered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…According to the current state of research, the prevalence for HMV varies widely: While Valko et al [ 4 ] estimated the prevalence for Hungary at 3.9/100,000 in 2018, Vitacca et al [ 5 ] estimated a prevalence of 63/100,000 in Italy in 2012. A Europe-wide study, which included 16 countries, mentioned a prevalence of 6.6/100,000 in 2005 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the current state of research, the prevalence for HMV varies widely: While Valko et al [ 4 ] estimated the prevalence for Hungary at 3.9/100,000 in 2018, Vitacca et al [ 5 ] estimated a prevalence of 63/100,000 in Italy in 2012. A Europe-wide study, which included 16 countries, mentioned a prevalence of 6.6/100,000 in 2005 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients with chronic respiratory failure needing home mechanical ventilation (HMV) is increasing. In the Eurovent analysis, published in 2005, the estimated prevalence of HMV in Europe ranged from 0.1 to 6.6 per 100 000 people [ 1 ]; however, more recent data showed prevalence ranging from 3.9 per 100 000 inhabitants in Hungary [ 2 ] and up to 63 per 100 000 inhabitants in Italy [ 3 ]. In well-described cohorts, it has been shown that HMV use has substantially increased since 2000 [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%